2008
DOI: 10.1002/bip.20919
|View full text |Cite
|
Sign up to set email alerts
|

Using peptides to study the interaction between the p53 tetramerization domain and HIV‐1 tat

Abstract: Peptides are valuable tools for studying protein-protein interactions, especially in cases of isolated protein domains and natively unfolded proteins. Here, we used peptides to quantitatively characterize the interaction between the natively unfolded HIV-1 Tat protein and the tetramerization domain of the cellular tumor suppressor protein p53. We used peptide mapping, fluorescence anisotropy, and NMR spectroscopy to perform a detailed structural and biophysical characterization of the interaction between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…We next examined whether p53 interacts directly with Tat protein. Direct interaction of p53 and Tat has been controversial (33)(34)(35), and we could not find any evidence of a direct interaction between p53 and Tat in coimmunoprecipitation (co-IP) assays or yeast two-hybrid analysis (data not shown). These data suggested that another factor(s) may be involved in p53-mediated Tat suppression rather than direct interactions between the two molecules.…”
Section: Hiv-1 Infection Activates P53 Which Inhibits Tat Functionmentioning
confidence: 81%
“…We next examined whether p53 interacts directly with Tat protein. Direct interaction of p53 and Tat has been controversial (33)(34)(35), and we could not find any evidence of a direct interaction between p53 and Tat in coimmunoprecipitation (co-IP) assays or yeast two-hybrid analysis (data not shown). These data suggested that another factor(s) may be involved in p53-mediated Tat suppression rather than direct interactions between the two molecules.…”
Section: Hiv-1 Infection Activates P53 Which Inhibits Tat Functionmentioning
confidence: 81%
“…The existence of large unstructured protein domains has recently been evidenced by NMR, for soluble proteins. It seems that unstructured protein domain, can fold upon contact with other proteins, as shown by the example of natively unfolded HIV-1 Tat protein and the tetramerization domains of the cellular tumor suppressor protein p53 [27]. It is therefore conceivable that the fine nanostructure of material surface can help folding protein domains that are unstructured in solution.…”
Section: 3mentioning
confidence: 99%
“…The effect was shown to be dependent on the p53 phosphorylation state [29]. Other proteins reported to bind to p53CTD are E3 ligases [30], [31], tumor suppressors [32] and viral proteins [33], [34].…”
Section: Introductionmentioning
confidence: 98%